Sanksi Pidana Terhadap Pelaku Tindak Pidana Perdagangan Orang - Rendi Salasbi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2022)
Trafficking in person is a crime that operates secretly, so that the community and LSM have the right to obtain legal protection and can assist authorized officers by providing information or reporting when they witness the crime of trafficking in person. The regulation of the criminal act of trafficking in persons before Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons is passed, the Penal Code Article 297 which reads Trafficking of women and boys who are not yet adults, is punishable by imprisonment of up to 6 years. Criminal sanctions against the perpetrators of the criminal act of trafiicking in persons include, among others, any person who recruits, sends, transfers, or receives a person with threats of violence, the use of force, kidnapping, imprisonment, forgery, fraud, abuse of power, paying even though obtaining approval from the person holding the control over another person, for the purpose of exploiting that person in the territory of the Republic of Indonesia, is sentenced to a minimum of 3 years and maximum of 15 years imprisonment, is subject to a fine of at least IDR 120,000,000 and maximum fine of IDR 600,000,00,-